Plantation forestry - Dhiman, R. C. (Indian Forester, 2021)
Plantation forestry has a very long history in India. Regular plantation work on forest land was started around 180 years back. The status of plantation forestry could be divided in three phases viz., pre-independent, post independent and current status. Initially, it was only the forest department that was engaged in raising forest plantations on forest land for wood and non wood products. Over the years the objectives for raising plantations and also the agencies engaged in such activity have vastly enlarged. Currently, the plantations are raised at a massive scale in agroforestry on farmland which is meeting around 90% of wood requirement of the country. Funds for plantation activities are now available from number of sources including national and state governments, international donor agencies, wood based industry and private sector among some others. A new term â€œOpportunistic Rotationâ€ is introduced, first time, to represent the production cycle followed for plantations grown on farmland. Paper further suggests some critical issues to create a reasonable balance between protection and production forestry to address the current forest based needs.